Realisasi Pembiayaan Pemilikan Rumah Subsidi berdasarkan Prinsip Perbankan Syariah (Lembaga Pengembangan Kinerja Dosen, 2023)
Bank Sulselbar is a bank owned by the regional government of South Sulawesi and West Sulawesi. Apart from being part of a BUMN that supports local government programs, it is also a regional autonomy tool that helps the regional economy. One of the missions carried out by Bank Sulselbar is as a Regional Development Bank that can provide support for regional development and support business development. One type of credit that is still in demand and needed by the community is KPR (House Ownership Credit). Mortgages by banks are further divided into two types, namely subsidized mortgages and non-subsidized mortgages. As a financial institution, the role of the Bank in the economy is very dominant. Therefore, this research will focus on: (1) Mechanisms of financing subsidized housing ownership at Bank Sulselbar sharia services Parepare Branch. (2) Islamic economic analysis of the mechanism for financing subsidized housing ownership at Bank Sulselbar sharia services Parepare Branch. In this study, the authors made direct observations of the object to be studied by seeing firsthand how the financing process for the financing mechanism for subsidized housing at the Bank Sulselbar sharia services Parepare Branch and the author will conduct direct interviews with employees of the Parepare Branch Sulselbar Bank. The results of the study show that the mechanism for financing mortgages at Bank Sulselbar Parepare branch is customer determination, analysis stages and the use of contracts which must also be in accordance with syar'i without violating the value of justice. Islamic Economic Analysis of the Mechanism of Financing for Subsidized Home Ownership at the Parepare Branch of Sulselbar Sharia Bank that if based on Q.S Al-Maidah, the murabahah mortgage financing carried out by the Parepare Branch of SulselBar Bank has carried out mutual assistance activities. Mutual assistance activities by helping to realize the customer's desire to be able to own a house even though the income is low